2016
DOI: 10.3389/fncir.2016.00011
|View full text |Cite
|
Sign up to set email alerts
|

Sparing of Descending Axons Rescues Interneuron Plasticity in the Lumbar Cord to Allow Adaptive Learning After Thoracic Spinal Cord Injury

Abstract: This study evaluated the role of spared axons on structural and behavioral neuroplasticity in the lumbar enlargement after a thoracic spinal cord injury (SCI). Previous work has demonstrated that recovery in the presence of spared axons after an incomplete lesion increases behavioral output after a subsequent complete spinal cord transection (TX). This suggests that spared axons direct adaptive changes in below-level neuronal networks of the lumbar cord. In response to spared fibers, we postulate that lumbar n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Early after injury, interneuron atrophy and abnormal synpatic formations were evident, with greater abnormalities occurring as severity increased. 44 Electrophysiological testing of the ankle dorsIflexor reflex showed marked hyperexcitability regardless of severity of SCI. 44 The test for segmental learning required the rat to learn to hold the paw above a saline solution to avoid a small shock to the tibialis anterior (TA).…”
Section: Spinal Cord Injurymentioning
confidence: 97%
“…Early after injury, interneuron atrophy and abnormal synpatic formations were evident, with greater abnormalities occurring as severity increased. 44 Electrophysiological testing of the ankle dorsIflexor reflex showed marked hyperexcitability regardless of severity of SCI. 44 The test for segmental learning required the rat to learn to hold the paw above a saline solution to avoid a small shock to the tibialis anterior (TA).…”
Section: Spinal Cord Injurymentioning
confidence: 97%
“…Spinal shock results from structural and biochemical indices of maladaptive neuroplasticity regulated by neuroinflammation. Findings of aberrant spine formations throughout dorsal, intermediate, and ventral neuron networks support this mechanism (Bandaru et al, 2015; Hains and Waxman, 2006; Hansen et al, 2016; Tan et al, 2008). We postulate that remote inflammatory signaling jeopardizes the homeostatic balance of excitatory and inhibitory synaptic contacts in locomotor networks after SCI.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, in our SCI model, we found that injury initiated the release of monocytes into circulation and that this was maintained through 7 dpi. Based on these findings, alongside work in our companion manuscript demonstrating segmental functional impairments in the lumbar cord (Hansen et al, 2016), we postulate that infiltrated macrophages around locomotor networks do not support adaptive function or repair. Instead, we suggest that lumbar macrophages take on a detrimental phenotype early after SCI that renders lumbar networks refractive to function and initiates an acute period of spinal shock.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Despite many examples of successful neurorehabilitative efforts to reengage locomotor activity, evidence suggests that neurorehabilitation in current settings has limited effectiveness. 60 Maladaptive forms of plasticity such as hyper-reflexia/spasticity and chronic central pain can emerge spontaneously after SCI, [61][62][63][64] and once established, maladaptive spinal cord plasticity may undermine the effectiveness of common forms of adaptive rehabilitation including stand training and swimming therapy. 65,66 Accumulating evidence suggests that afferent input in the acute phase of injury can also contribute to maladaptive forms of plasticity, thus making attempts at later adaptive training more difficult.…”
Section: Maladaptive Plasticitymentioning
confidence: 99%